Studi Perbandingan Analisa Pemilihan Rute Jalan Tol Krian – Legundi – Bunder – Manyar Berdasarkan Karakteristik Jalan dan Pengguna Jalan - Yanida Agustina; Hera Widyastuti (Jurnal Aplikasi Teknik Sipil, 2023)
KLBM Toll Road is one of the Non-Trans-Java Toll Road projects connecting Sidoarjo Regency and Gresik Regency. The demand of toll roads needs to be considered in toll road planning. Traffic assignment analysis is carried out by calculating the benefits given due to the characteristics of a road. While the characteristics of road users are not accommodated in the road infrastructure planning and result in "optimism bias". So there is a need for a study that analyzes the differences in traffic assignment analysis based on road characteristics and road users. The probabilities obtained from JICA I method analysis has significant difference towards stated preference method. The significant difference result is due to differences in the characteristics used, namely the characteristics of the road and the resulting cost savings on the perceptions and characteristics of road users.